OPTIMALISASI ON LINE SYSTEM REGISTRASI KENDARAAN BERMOTOR DALAM RANGKA PENANGGULANGAN TINDAK PIDANA PEMALSUAN DOKUMEN DI SAMSAT MEDAN - Riduan Riduan; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
The application of an on-line system in the field of Regident Ranmor has been carried out at the Traffic Directorate level with various strategic alignments in public service management which are translated into criteria such as competitive advantage, timeliness of service fulfillment, community satisfaction, labor productivity and profitability, but on line system as an effort to achieve the effectiveness of regindent ranmor services related to information technology development products to improve service quality and the management of information technology operations is currently still not optimal. The research method used in this thesis research is descriptiveanalytical with normative legal research. Based on the results of the research it was found that the crime of counterfeiting or abbreviated as the crime of counterfeiting is a crime in which there is a system of untruth or falsehood of a thing (object) that something appears from the outside as if it is true, even though in fact it is contrary to the truth. Countermeasures against the Crime of Forgery of Documents Through Optimization of the On Line System as a Non Penal Policy effort through a broader, strategic, integrated and controlled HTCK (Work Procedure Relations) in an on-line system for the development of an applicant identity data collection system at Dirlantas Poldasu with the Regional Revenue Service including with the Population Service in the Provsu area, for example making SOPs and Jukrah for handling KTP misuse found atthe request of the applicant for registration and identification of motorized vehicles at the time of registration, validation of STNK and payment of motor vehicle taxes. In addition, it is necessary to develop an on line system through the Secure Access Module (SAM)